Does the Cyanophora paradoxa genome revise our view on the evolution of photorespiratory enzymes?. (2nd April 2013) - Kern, R.; Eisenhut, M.; Bauwe, H.; Weber, A. P. M.; Hagemann, M.
Abstract: In the present‐day O2 ‐rich atmosphere, the photorespiratory pathway is essential for organisms performing oxygenic photosynthesis; i.e. cyanobacteria, algae and land plants. The presence of enzymes for the plant‐like 2‐phosphoglycolate cycle in cyanobacteria indicates that, together with oxygenic photosynthesis, genes for photorespiratory enzymes were endosymbiotically conveyed from ancient cyanobacteria to photosynthetic eukaryotes. The genome information for Cyanophora paradoxa, a member of the Glaucophyta representing the first branching group of primary endosymbionts, and for many other eukaryotic algae was used to shed light on the evolutionary relationship of photorespiratory enzymes among oxygenic phototrophs. For example, it became possible to analyse the phylogenies of 2‐phosphoglycolate phosphatase, serine:glyoxylate aminotransferase and hydroxypyruvate reductase. Analysis of the Cyanophora genome provided clear evidence that some photorespiratory enzymes originally acquired from cyanobacteria were lost, e.g . glycerate 3‐kinase, while others were replaced by the corresponding enzymes from the α‐proteobacterial endosymbiont, e.g . serine:glyoxylate aminotransferase. Generally, our analysis supports the view that many C2 cycle enzymes in eukaryotic phototrophs were obtained from the cyanobacterial endosymbiont, but during the subsequent evolution of algae and land plants multiple losses and replacements occurred, which resulted in a reticulate provenance of photorespiratory enzymes with different origins in different cellular compartments.